Sinology at the phylology faculty of the Belarusian State University: history, current state and prospects - Zhukavets, Veronika V.; Khmialnitski, Mikalai M. (Journal of the Belarusian State University. Philology, 2021)
This article focuses on the history of the origin and development of sinology at the faculty of philology of the Belarusian State University. The main methodological models, modern educational technologies used in teaching students of the specialty 1-21 05 06 «Chinese philology» have been determined. This article describes the main directions of educational, methodological, scientific, cultural and educational activities of the department of Chinese philology that was founded in 2011. Academic staff of the department participate in systematic research of the Chinese-Belarusian linguistics, literary and cultural connections, problems of literary translation; make research in the field of methodology of teaching the Chinese language and literature in secondary schools and higher educational institutions of the Republic of Belarus. The results of the research have become foundational in these directions. The main achievements of the twenty-year period of teaching sinology in the faculty of philology have been noted. The article emphasises the demand for graduates in the modern labour market, system of education and humanities in general.